2019
DOI: 10.3390/ani9090658
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Sows into Alternative Lactation Housing Affects Sow Aggression at Mixing, Future Reproduction and Piglet Injury, with Marked Differences between Multisuckle and Sow Separation Systems

Abstract: Simple SummaryAlternative lactation housing could reduce aggression when sows are mixed. We aimed to compare the effects of mixing sows during lactation (with or without piglets) at weaning and after insemination and determine the effects of mixing strategies and lactation housing on the piglet. Sows in the multisuckle treatment were the least aggressive, had the fewest injuries around mixing, and gave birth to the most piglets at the subsequent litter, with multisuckle housing having no apparent ill effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, there is evidence that OXT participates in the control of emotionality in mammals. During early lactation maternal aggression towards intruders and the defense of the young is high in rats, 48,49 sows, 50,51 and rabbits 52–54 . Ibotenic acid lesions of the PVN or infusion of antisense oligonucleotides against OXT into this nucleus increases maternal aggression in rats when these procedures are performed on the fifth, but not on the 18th day of lactation 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is evidence that OXT participates in the control of emotionality in mammals. During early lactation maternal aggression towards intruders and the defense of the young is high in rats, 48,49 sows, 50,51 and rabbits 52–54 . Ibotenic acid lesions of the PVN or infusion of antisense oligonucleotides against OXT into this nucleus increases maternal aggression in rats when these procedures are performed on the fifth, but not on the 18th day of lactation 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Possible interactions between these two factors were not statistically significant (F[1, 53] = 0.692, p = .410). On day 2 a significant effect of parity was evident, as primiparous rabbits showed a significantly longer latency to enter the nest box (F[1,50] = 4.667, p = .036). No significant effects were found in relation to: (a) the injected agent (F [1, 50] = 2.606, p = .113); (b) an interaction between injected drug and parity (F[1, 50] = 2.606, p = .113).…”
mentioning
confidence: 99%
“…The main objective of the co-mingling of non-littermates prior to weaning is to ameliorate the weaning transition in order to reduce GIT dysbiosis and maintain optimal production. The co-mingling of non-littermates does not commonly affect the performance of piglets before weaning [97,104,138], although some studies have reported lower weaning weights and pre-weaning weight gains in socialized piglets compared with non-socialized piglets [44,76,92,127]. According to the authors, this could be due to a myriad of factors, including: the timing of co-mingling; higher space allowances and, therefore, more exercise; lower creep feed intake; disruption of suckling; cross-suckling; enhanced active behaviors; greater occurrence of fighting behaviors (skin lesions); relocation of the sows during co-mingling within the co-mingling group and, consequently, a high incidence of cross-suckling; and/or stress on the piglets due to the introduction of the piglets into new accommodation and environments after moving the sows and their litters from conventional housing to group lactation.…”
Section: Effects Of Co-mingling Before Weaning On Social Behavior Bef...mentioning
confidence: 99%
“…(Lange et al, 2021) or day 28 p.p. (Kutzer et al, 2009;de Ruyter et al, 2017;Greenwood et al, 2019), or to a 'long lactation' with weaning on for example day 34 p.p. , day 35 p.p.…”
Section: Weaningmentioning
confidence: 99%